(untitled) (Proceedings of the International Conference on Poverty and Sustainable Development, 2019)
The present study aims to identify the main strengths and weaknesses of Café Compadre social business and to design potential strategies to assist stakeholders to improve this coffee value chain. Based on the methodology proposed by E. Monastyrnaya et al. (2017), interviews to the stakeholders were conducted to identify the needs for sustainability. Later, potential solutions were proposed and the responsibilities were assigned to each actor for the process of the sustainable value creation. Results showed that the main strengths of this value chain are the environmental perspective (solar energy and GHG emissions reduction) and the social perspective (coffee farmers empowerment and higher income). However, different other values destroyed that included a deficient supply chain management were identified. For a better coffee production performance based on Café Compadre value chain, a joint development practice based on a collaboration strategy is required for the development of new technologies, processes and products. Recommendations included a long term relationship between stakeholders that is critical for the success of this social business.